Beispiel Nr: 09
$ \text{Gegeben:} ax^{3}+bx^{2}+cx+d=0 \\ \text{Gesucht:} \\ \text{Lösung der Gleichung} \\ \\ \\ \textbf{Gegeben:} \\ \frac{1}{2}x^3+4 =0\\ \\ \textbf{Rechnung:} \\\\ \frac{1}{2}x^3+4=0 \frac{1}{2}x^3+4 =0 \qquad /-4 \\ \frac{1}{2}x^3= -4 \qquad /:\frac{1}{2} \\ x^3=\displaystyle\frac{-4}{\frac{1}{2}} \\ x=\sqrt[3]{-8} \\ x=-2 \\ \text{Polynomdivision:}(-2)\\ \small \begin{matrix} ( \frac{1}{2}x^3&&&+4&):( x +2 )= \frac{1}{2}x^2 -1x +2 \\ \,-( \frac{1}{2}x^3&+x^2) \\ \hline &-1x^2&&+4&\\ &-(-1x^2&-2x) \\ \hline && 2x&+4&\\ &&-( 2x&+4) \\ \hline &&&0\\ \end{matrix} \\ \normalsize \\ \frac{1}{2}x^{2}-1x+2 =0\\ x_{1/2}=\displaystyle\frac{+1 \pm\sqrt{\left(-1\right)^{2}-4 \cdot \frac{1}{2} \cdot 2}}{2\cdot\frac{1}{2}}\\ x_{1/2}=\displaystyle \frac{+1 \pm\sqrt{-3}}{1}\\ \text{Diskriminante negativ keine Lösung} \\ \underline{x_1=-2; \quad1\text{-fache Nullstelle}} \\$